Analisis Kesulitan Pemahaman Konsep pada Materi Pythagoras di Kelas VIII SMP Negeri 3 Kartasura - Anggraini, Githa Randu, Drs. Ariyanto, M.Pd (2017)
The purpose of research is to describe the students' understanding of the concept of Pythagoras on the aspects to understand and apply aspects. This type of research is based on qualitative ethnographic design. When the study in the first semester of the year 2016/2017. The research subject teachers and students of SMP Negeri 3 Kartasura. Test data collection techniques, interviews and documentation. The validity of the data using a triangulation of sources and techniques. Data were analyzed using method three grooves. Research results based aspect to understand and implement aspects of states that students experience difficulties in operating algebra, determining Hypotenuse and express an idea. A good mastery of the material will be able to bring the students in producing a good resolution anyway.